Design and synthesis of PtPdNiCoMn high-entropy alloy electrocatalyst for enhanced alkaline hydrogen evolution reaction: a theoretically supported predictive design approach - Chandran, M. Athira; Dutta, Pritha; Singh, Prashant; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (Advanced Functional Materials, 2025)
Electrocatalytic hydrogen generation requires a cutting-edge, multifunctional electrocatalyst with abundant active sites to drive multielectron transfer reactions. High entropy alloys (HEA) are complex five or more-element alloy systems with high configurational entropy which makes them unique materials for next-generation electrocatalysts. Here, in this work, based on new screening guidelines for catalyst selections that combine density-functional theory calculated Gibbs formation-enthalpy with bond length and electronegativity variance, a novel HEA electrocatalyst consisting of five elements, namely, Pt, Pd, Ni, Co, and Mn is designed. By simple room temperature electrodeposition, the designed catalyst is prepared and its hydrogen evolution reaction (HER) is explored and validated through experimental and theoretical approaches. The HEA demonstrated a superior HER activity with an overpotential of 22.6 mV at -10 mA cm-2 which outperforms Pt/C commercial catalyst. No evident degradation of the material is detected even after 100 hours of continuous operation under high current density. Moreover, the HEA has shown exceptional performance in harsh electrolyte conditions such as in simulated seawater and actual seawater. Remarkably, the density-functional theory calculated small Gibbs formation-enthalpy (approximate to 0 eV) compared to Pt/C places the new HEA near the apex of Trasatti's model of Volcano plot, which is also suggestive of superior HER activity.
Keywords: DFT; electrocatalysts; Electronic Structure; HER; high-entropy alloys

Platinum-free electrocatalysts based on electrodeposited Co-Mn-Ni alloys for efficient electrocatalytic alkaline water splitting - Chandran, M. Athira; Dutta, Pritha; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (ACS Applied Energy Materials, 2025)
The development of a Pt-free electrocatalyst for efficient and stable water splitting is crucial for the commercialization of green hydrogen production. A low-cost electrocatalyst with good hydrogen and oxygen evolution activities (HER and OER, respectively) displaying long durability is the first step in this direction, and if the catalyst can be synthesized via an easy, convenient, and scalable procedure, that would be an added advantage. Multicomponent alloys, with their tunable compositions and abundant active sites, present a promising solution in this direction. Herein, a cost-effective CoMnNi (CMN) alloy is synthesized via electrodeposition and with optimized composition by tuning the electrolyte concentration and deposition potential to enhance electrocatalytic performance. The resulting single-phase alloy exhibits a high electrochemical surface area with an average particle size of similar to 4 nm, demonstrating excellent hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities in 1 M KOH, with overpotentials of 121 mV at -10 mA cm-2 and 285 mV at 20 mA cm-2, respectively. Moreover, the catalyst exhibits remarkable stability, sustaining 100 h of operation at 100 mA cm-2. The CMN alloy also performs efficiently under harsh conditions, including 6 M KOH and alkaline seawater, in both symmetric and asymmetric cell configurations. This work highlights the potential of multicomponent alloys as durable, high-performance electrocatalysts for scalable water splitting, paving the way for sustainable hydrogen production.
Keywords: alkaline seawater; electrocatalysis; Electrodeposition; hydrogen evolution reaction(HER); multicomponentalloy; oxygen evolution reaction (OER); stability; watersplitting